Exploring the uses of mobile apps by Portuguese students during COVID-19 pandemic - Gomes, Natalia (2022)
The Covid-19 pandemic has been a real-time laboratory for a technological future that Anderson, Rainie and Vogels (2021) describe as "tele-everything". Among other mediated practices, online shopping, virtual schooling, teleworking, telehealth, online workout, and even virtual parties were adopted in unprecedented ways to avoid physical contact during the outbreak. The pandemic has pushed people into new socially mediated practices and posed demanding challenges to those who had difficulties dealing with internet addiction or separating work time from leisure. Despite the surge of various studies about Covid-19 tracing apps, there is a lack of studies regarding students' use of mobile apps during the lockdown. Considering the ubiquitous presence of smartphones in the students' lives (Silver et al., 2019), mobile apps have been the proxy for reconfiguring the relationships between students, their families and teachers, studying routines and other social practices. This exploratory study seeks to understand the role of mobile apps in the lives of Portuguese higher education students during the period of social isolation caused by the Covid-19 pandemic. The empirical research draws on a quantitative methodology through an online questionnaire applied during the first state of emergency declared by the Portuguese Government in early 2020. A snowball process was used to gather a non-probabilistic sample (N=88), and data were analysed using descriptive statistical analysis. The results indicate that most respondents (77.2%) intensified the use of mobile apps in this period. Nevertheless, there is a considerable perception (59%) that these patterns of use of mobile apps are a waste of time